2016
DOI: 10.1007/s11356-016-7900-x
|View full text |Cite
|
Sign up to set email alerts
|

Fe deficiency induced changes in rice (Oryza sativa L.) thylakoids

Abstract: Iron deficiency is an important abiotic stress that limits productivity of crops all over the world. We selected a hybrid rice (Oryza sativa L.), LYPJ, which is super high-yield and widely cultured in China, to investigate changes in the components and structure of thylakoid membranes and photosynthetic performance in response to iron deficiency. Our results demonstrated that photosystem I (PSI) is the primary target for iron deficiency, while the changes in photosystem II (PSII) are important for rebuilding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…Plantlets were harvested at 10: 00 AM at 15 DPI for Chlorophyll a fluorescence measurement using a Handy-PEA instrument (Handy PEA, Hansatech, United Kingdom) (Wang et al, 2017). Prior to measurement, A. lances leaves were dark-adapted for 30 min at room temperature to relax the reaction centers.…”
Section: Methodsmentioning
confidence: 99%
“…Plantlets were harvested at 10: 00 AM at 15 DPI for Chlorophyll a fluorescence measurement using a Handy-PEA instrument (Handy PEA, Hansatech, United Kingdom) (Wang et al, 2017). Prior to measurement, A. lances leaves were dark-adapted for 30 min at room temperature to relax the reaction centers.…”
Section: Methodsmentioning
confidence: 99%
“…However, iron, which is a micronutrient is often required in small quantities, though it plays a major role in photosynthetic electron transport. It is one of the most important elements involved in chlorophyll formation, photosynthesis, and the photosynthetic enzyme (i.e., ribulose 1,5-bisphosphate carboxylase/oxygenase) in the plant (Wang et al, 2017;Yoon et al, 2019;Maitra et al, 2022). Iron also plays a pivotal role in nitrogen assimilation, uptake, and translocation by regulating the cofactor enzymes of nitrogen metabolism [i.e., nitrate reductase (NR), nitrite reductase (NiR), and glutamate synthase (GOGAT)] (Borlotti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, Fe is essential to perform various cellular processes, such as respiration and photosynthesis. It also serves as a cofactor for enzymes such as cytochrome P450s and Fe­(II)/2-oxoglutarate-dependent oxygenases and helps to remove a kinetic barrier of enzymatic reactions, which involves electron-transfer or oxygen-transfer processes. , Gibberellic acid (GA), jasmonic acid (JA), and salicylic acid (SA) have critical roles in Fe homeostasis in plants. , Recent studies demonstrated that Fe provides added immunity to plants against biotic stresses, and its deficiency causes abiotic stress. , The effects of Fe deficiency on the major plant defense hormones such as SA and JA have been more clearly understood in recent years . It has been found that Fe deficiency enhances SA accumulation in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Recent studies demonstrated that Fe provides added immunity to plants against biotic stresses, and its deficiency causes abiotic stress. 9,10 The effects of Fe deficiency on the major plant defense hormones such as SA and JA have been more clearly understood in recent years. 5 It has been found that Fe deficiency enhances SA accumulation in Arabidopsis.…”
Section: ■ Introductionmentioning
confidence: 99%